„Wykaz doktoratów Wydziału Teologicznego Uniwersytetu Mikołaja Kopernika w Toruniu z lat 2003-2010” - Krajniak, Weronika (Archiwa, Biblioteki i Muzea Kościelne, 2016)
The article entitled " The list of doctoral theses of the Faculty of Theology at Nicolaus Copernicus University in Toruń in the years 2003-2010" is a summary of doctoral theses stored in the University Archive. The list includes the following elements: the name and surname of the author, the information on whether the author is a lay person or a cleric one, the title of the thesis, the name of the supervisor, the names of the reviewers, the date of defence, the number of pages and the archival reference number. Additionally, footnotes include the information about the works which were published, presenting their full bibliographic description.